Matching the quark model to the 1/Nc expansion - Pirjol, D. (2011)
We compute the coefficients of the effective mass operator of the 1/N c expansion for negative parity L=1 excited baryons using the Isgur-Karl model in order to compare the general approach, where the coefficients are obtained by fitting to data, with a specific constituent quark model calculation. We discuss the physics behind the fitted coefficients for the scalar part of the most general two-body quark-quark interaction. We find that both pion exchange and gluon exchange lead to the dominance of the same operator at the level of the effective mass operator, which is also observed from data. © 2011 American Institute of Physics.